2000
DOI: 10.1103/physrevb.62.1186
|View full text |Cite
|
Sign up to set email alerts
|

Current and power spectrum in a magnetic tunnel device with an atomic-size spacer

Abstract: Current and its noise in a ferromagnetic double tunnel barrier device with a small spacer particle were studied in the framework of the sequential tunneling approach. Analytical formulae were derived for electron tunneling through the spacer particle containing only a single energy level. It was shown that Coulomb interactions of electrons with a different spin orientation lead to an increase of the tunnel magnetoresistance. Interactions can also be responsible for the negative differential resistance. A curre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
141
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(142 citation statements)
references
References 27 publications
1
141
0
Order By: Relevance
“…It turns out that measurement of the shot noise provides additional information on quantum and Coulomb correlations, which is not accessible in the measurements of average current. [1][2][3][4][5][6][7][8][9][10][11][12][13] The noise measurements are especially important for the physics of mesoscopic structures, where the current fluctuations are expected to be strongly enhanced. 1 The shot noise in mesoscopic conductors was studied theoretically more than two decades ago in the pioneer works of Lesovik 2 and Büttiker et al 3,4 Various aspects of the shot noise and its manifestation in transport characteristics of normal-metallic, semiconducting, and superconducting structures have been reviewed by Blanter and Büttiker.…”
Section: Introductionmentioning
confidence: 99%
“…It turns out that measurement of the shot noise provides additional information on quantum and Coulomb correlations, which is not accessible in the measurements of average current. [1][2][3][4][5][6][7][8][9][10][11][12][13] The noise measurements are especially important for the physics of mesoscopic structures, where the current fluctuations are expected to be strongly enhanced. 1 The shot noise in mesoscopic conductors was studied theoretically more than two decades ago in the pioneer works of Lesovik 2 and Büttiker et al 3,4 Various aspects of the shot noise and its manifestation in transport characteristics of normal-metallic, semiconducting, and superconducting structures have been reviewed by Blanter and Büttiker.…”
Section: Introductionmentioning
confidence: 99%
“…However, several theoretical works on various systems have showed that Coulomb interactions might also lead to a super-Poisson shot noise with a Fano factor F > 1. Examples of such systems are quantum dots that are coupled to ferromagnetic leads [7][8][9][10] , multi-levels quantum dots 11,12 , multidots structures [13][14][15][16][17][18] , and also three terminal quantum dots [19][20][21] . There are also experimental works [22][23][24][25][26] in which a super-Poisson noise was measured in quantum dots, rather than the sub-Poisson noise, which is expected from the single level model of the quantum dots.…”
Section: Introductionmentioning
confidence: 99%
“…[17], and they were found to be negative. The noise of a twoterminal quantum dot with ferromagnetic contacts was studied in the sequential tunneling limit [18,19], and, interestingly, a super-Poissonian Fano factor was found.In this Letter, we consider an interacting threeterminal quantum dot with ferromagnetic leads. The dot is operated as a beam splitter: one contact acts as source and the other two as drains.…”
mentioning
confidence: 99%
“…[17], and they were found to be negative. The noise of a twoterminal quantum dot with ferromagnetic contacts was studied in the sequential tunneling limit [18,19], and, interestingly, a super-Poissonian Fano factor was found.…”
mentioning
confidence: 99%